DINAMIKA MANAGEMENT KONFLIK SOSIAL MESUJI DI PROVINSI LAMPUNG - Puguh Santoso; Pujo Widodo; Herlina Juni Risma Saragih; Habib Rahman Nugraha (CV. AFDIFAL MAJU BERKAH, 2023)
This research is discusses about Dynamics Of Mesuji Social Conflict Management In Lampung Province. Using CEWERS and Management Conflict as Theory and Concept, then the purpose of this research is to discuss and explore more how to solve the agrarian conflict that happen in Lampung Province. The method of writing this research is using qualitative research methods and data collection techniques in the form of Literature Studies and Library Research. This literature research was obtained from various articles in the 2010 to 2021 time frame. Actually humans cannot be separated from problems or conflicts, the best solution is how to control it. The conclusion and recommendation of this research are that the agrarian conflict here is really comprehensive because it is between conflicts horizontal conflict with vertical conflict, there is even a third party, namely the owner of capital which are not only from within the country, but involve foreign parties. So it need take an action from all elements of society to make it happen peace and social welfare in the Mesuji district. Starting from synergy between Central Government and Local Government, Corporate Transparency or entrepreneurs, the alertness of law enforcement officers and of course the understanding of local residents.